Failed Loop Endobutton Acromioclavicular Joint Reconstruction Treated with Duo Figure of 8 FiberTape Augmented Autogenic Graft Wrapping Technique: A Case Report - Saurabh Singh; Sushit Kumar Sonu; Rahul Patel; Kumar Prashant; Himanshu Nagar (Journal of Orthopaedic Case Reports)
Introduction: Acromioclavicular joint (ACJ) injuries are prevalent among young, active individuals and account for a significant proportion of shoulder girdle and collision sports injuries. The Rockwood classification system categorizes these injuries from Type I to VI, guiding treatment from conservative management to surgical intervention. Despite various surgical techniques, including the Fiber-loop Endobutton method, failure rates, and complications remain a concern, particularly in cases of post-operative instability. Case Report: A 50-year-old male presented with persistent right shoulder pain and deformity following an initial Type-V ACJ injury from a road traffic accident. The patient had undergone surgical stabilization with a Fiber-loop Endobutton construct. However, 17th days post-surgery, he experienced a recurrence of pain and deformity, with radiographs revealing the failure of the initial repair. Subsequent imaging indicated a mal-positioned Endobutton and potential coracoid blowout, likely due to inadequate drill hole placement. Three weeks later, the patient underwent revision surgery using a double figure-of-8 autogenic loop reconstruction with FiberTape and hamstring tendon graft. The procedure involved removing the failed hardware, drilling new holes in the clavicle, and securing the ACJ with FiberTape and a hamstring graft. The graft was looped around the coracoid and clavicle in a figure-of-8 manner to replicate acromioclavicular ligament anatomy and ensure both horizontal and vertical stability. At 6 weeks, follow-up radiographs demonstrated near-anatomic alignment of the ACJ and coracoclavicular. The patient reported minimal pain and regained a near-full range of motion. By 6 months, while slight radiographic changes were noted, the patient remained asymptomatic with excellent functional outcomes and minimal limitations. Conclusion: This case highlights the challenges of managing post-operative instability in ACJ injuries. The successful use of a dual figure-of-8 graft technique provides a viable solution for revision surgery, offering satisfactory stability and functional recovery. Further research is needed to optimize salvage techniques for complex cases.